SISTEM INFORMASI PENGAJUAN DAN PENGADUAN MASAYARAKAT PADA KECAMATAN SUMBER WRINGIN - Wahyudi, Fitradyah Ika; Lutfi, Ahmad; Azise, Nur (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2024)
The development of information technology is growing rapidly and has significance in various aspects of life, including the fields of education, economics, politics, social and culture. In the government sector, fast, accurate and efficient data management is needed to support and simplify work processes in serving the community. The website is one option that can be used to process public submissions and complaints to government institutions. The design of this public submission and complaint information system aims to help the public convey their aspirations easily and quickly. The results of the website design will be used as a medium for the public submission and complaint process and fast responsiveness from government institutions. The method used in website design is the waterfall method which consists of analysis, design, coding, testing and support. It is hoped that website design can be a solution to the lengthy process of public complaints to government institutions.